Analisis Beban Kerja Tenaga Harian Lepas Pelayanan Persampahan/ Kebersihan Dan Pelayanan Pertamanan Di Dinas Lingkungan Hidup Kabupaten Langkat - Muhammad Harmain; Nina Siti Samaniah Siregar; Rudi Salam Sinaga (Universitas Medan Area, 2025)
This study aims to analyze the workload of daily workers in waste management/cleaning and landscaping services at the Environmental Office of Langkat Regency. Daily workers play a crucial role in maintaining environmental cleanliness and aesthetics, yet face challenges such as heavy workloads, limited human resources, and inadequate equipment. Using a qualitative approach, data were collected through in-depth interviews and direct field observations. The results indicate that the heavy workload is due to the large volume of tasks, uneven work distribution, and lack of attention to workers' welfare, leading to physical exhaustion and mental stress. The study recommends increasing workforce capacity, improving facilities, and reviewing workload management policies to enhance efficiency, improve the welfare of daily workers, and optimize service delivery.